BEHAVIOR SPEECH COMMUNICATION OF PASAMBAHAN BATIMBANG TANDO (ENGAGEE) IN MINANGKABAU CULTURE IN PARIAMAN – WEST SUMATERA - Asvisari, Yulisa; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Tradition of Pasambahan Batimbang Tando in Village Tandikat is done as for generations consist of values and norms of culture. The research purpose to know behavior speech of Pasambahan Batimbang Tando in Minangkabau Culture, West Sumatera. To reach the purpose is given question about situation of communications, communicative event and communicative measure about Pasambahan Batimbang Tando in Culture Village Tandikat Kabupaten Pariaman.The method used in this research is qualitative method communication ethnography tradition. The data is collected through observation and interview. Subject of research is people in Village Tandikat from seven informant, consist of four juru sambah and three people understanding and knowing about Pasambahan Batimbang Tando. Collect data technical via personal interview, participant observation, field note, library study, documentation, and internet searching. Test to legitimate data used triangulasi and member checking technic.The result of this research can be used to know communication activity in Pasambahan Batimbang Tando in Village Tandikat, Patamuan Kabupaten Pariaman, West Sumatera presenting things in Culture discussion. It is done according to ritual by juru sambah between man’s family dan woman’s family to reach a deal. After that, the relationship can be continued to serious relation to get married.Keyword : pasambahan batimbang tando (pertunangan), tradition, communication ethnography